KONSTRUKSI HUKUM DALAM PEMBUKTIAN UNSUR TINDAK PIDANA PEMBUNUHAN BERENCANA - Hajairin, Hajairin (SANGAJI: Jurnal Pemikiran Syariah dan Hukum, 2017)
In this research, the author saw in two court judgments which taken out by the District Court (PN) of Raba Bima, number 341/Pid.B/2014/PN.R.bi and the High Court of Mataram (PT), number 20/Pid/2015/PT.Mtr. Both of judgments are strengthen each other, it defendant is in the period of detention during 19 years in prison. However, the verdict/judgment of Supreme Court Number 815K/Pid/2015 cancelled of two court judgment which it underneath. In this case, the Judge has different view of law as the main point to be consideration to make decision for Abdul Khalik. The construction of law in this case has to be seen and translated by the concept of judgment and legal certainty, because of different decision making by District Court (PN) of Raba Bima, the High Court of Mataram and Supreme Court which is freeing Abdul Khalik from all lawsuits. Based on these situation, it need to deep analysis and critically to get the best judgment as the goal of criminal law which is born by the criminal justice system.